TUBERCULOSIS PATIENTS' KNOWLEDGE, ATTITUDE AND PRACTICE OF COUGH ETIQUETTEA IN PRIMARY HEALTH CARE DISTRICT OF BANDUNG - Desy Indra Yani; Yayat Fajar Hidayat; Afif Amir Amrullah (Belitung Raya Foundation, 2018)
Background: Tuberculosis (TB) is the major global health problem. A high number of TB cases are as a result of the disease spreads through droplet nuclei which mainly through a cough. TB transmission prevention is really important to lower the rate of new infection. Since TB transmission is through a cough, therefore, one of the preventions behaviour is implementing the good and right cough etiquette. In 2016 there were 425 TB patients in Sub-District Rancaekek and was the higher number in District of Bandung. The aim of this study was to find out the overview of knowledge, attitude and practice of cough etiquette in tuberculosis patients. Objectives: The aim of this study was to find out the overview of knowledge, attitude and practice of cough etiquette in tuberculosis patients. Methods: This study was descriptive quantitative with the cross sectional approach, the population were all Acid-Fast Bacillus (AFB) + TB patients that were registered in the primary health care Rancaekek, Linggar and Nanjung Mekar amount of 52 people and used total sampling. The data collection technique used a questionnaire to measure knowledge and attitude, and observation sheet to measure practice that was valid and reliable. The used data analysis was frequency distribution, mean and median. Results: The results of this study indicated that from 52 respondents, more than half of them had good knowledge about cough etiquette (65.4%, median value 83.33 and IQR 20), more than half of them had negative cough etiquette attitude (51.9%, mean value 47.87 and SD 5.885) and more than half of them had bad practice in cough etiquette (63.5%, median value 5 and IQR 2). Conclusions: The result of this study is expected to become an overview for primary health care in doing improvement in delivering education to TB patients and their families about the good and right cough etiquette which is focused on the affective and psychomotor aspects, such as lectures, leaflet distribution, and live right and good cough etiquette simulation, so that it can prevent the spread of TB and decrease the rate of TB infection.